Multidimensional bandwagon effect and dual-process decision making: An integrated model of the theory of planned behavior from the perspective of American millennials’ travel intention - Roannayutt Oan-Oon; Therdchai Choibamroong (Heliyon)
This study addresses the imperative need for an updated approach that incorporates evolving psychological insights and economic theories to better understand decision-making processes in the tourism sector. By integrating the bandwagon effect with the theory of planned behavior (TPB), the study aims to gain deeper insights into the intention-forming processes of American millennials during the pre-trip stage when considering a visit to Thailand. The research amalgamates principles from behavioral economics and traditional psychological theory within the dual-process framework, providing a comprehensive understanding of how American millennials determine their visit intention. Through empirical analysis employing Partial Least Squares Structural Equation Modeling (PLS-SEM) in a post-pandemic context, the study reveals that the multidimensional bandwagon effect significantly and synergistically influences American millennials' travel intention, attitude, and subjective norm, supporting a dual-process decision-making model. These findings elucidate how American millennials navigate heuristics and cognitive biases based on the theory of planned behavior framework, offering valuable insights for destination management organizations to refine their marketing and communication strategies effectively.